The species of Hippolyte Leach (Crustacea, Caridea, Hippolytidae) from Terminos Lagoon, southwestern Gulf of Mexico - Negreiros-Fransozo, M.L [UNESP]; Barba, E; Sanchez, A.J; Fransozo, Adilson [UNESP]; Ráz-Guzmán, A (Sociedade Brasileira de Zoologia, 1996)
The taxonomic identity of specimens of the genus Hippolyte Leach, 1814 of Laguna de Términos was considered including the colour and the presence-absence of tufts of plumose setae on the dorsal surface of the carapace and abdomen as secondary characteristics to morphological features of taxonomic value. Two groups were formed based on appearance: one transparent with setae and another green without setae. The analysis of five morphological characteristics in adult females of the two groups made it possible to identify only H. zostericola (Smith, 1873). Fecundity and fertility were similar (0.5>p>0.2) in both groups. The first zoea of both groups were also morphologically similar. Considering these results, it is concluded that the only species collected was H. zoslericola and that it has two phenotypical types. It is recomended that the morphological analysis of all larval stages be carried out.
Keywords: Hippolyte; zoea; fertility; fecundity; SW Gulf of Mexico